The Role of Quadruple Helix in Supporting Sustainability of Culinary Business - Windhyastiti, Irany; Khouroh, Umu; Aristanto, Eko (Proceedings of International Conference of Graduate School on Sustainability, 2022)
The number of food and beverage MSEs in East Java occupies the second highest position in Indonesia with a total of 746,732. But unfortunately, during the pandemic, food/beverage MSMEs (both packaged food/beverage home industries as well as coffee shop businesses, depots, and cafes) experienced an average decline of 63%. The condition of uncertainty due to the pandemic, which has forced the Government in each region to periodically issue PPKM policies, according to the level of conditions for the spread of Covid-19, has caused MSME actors to experience ups and downs in income. Therefore, to help minimize business losses in addition to creativity and innovation, business actors also need support from various parties, including the government, academics, and the community (Quadruple Helix). This study aims to analyze how big the role of government, academics, and the community has been shown so far and what business actors need for the role of government, academics, and the community. Keywords: Academics, Business Actors, Community, Government, Quadruple Helix